2015
DOI: 10.1159/000430143
|View full text |Cite
|
Sign up to set email alerts
|

PGE2 Modulates GABAA Receptors via an EP1 Receptor-Mediated Signaling Pathway

Abstract: Aims: PGE2 is one of the most abundant prostanoids in mammalian tissues, but its effect on neuronal receptors has not been well investigated. This study examines the effect of PGE2 on GABAA receptor currents in rat cerebellar granule neurons. Methods: GABAA currents were recorded using a patch-clamp technique. Cell surface and total protein of GABAA β1/2/3 subunits was carried out by Western blot analysis. Results: Upon incubation of neurons with PGE2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Similar to pro-inflammatory cytokines, PGE 2 can alter neuronal excitability and neurotransmission. PGE 2 has been shown to both enhance and inhibit glutaminergic transmission, depress glycingeric signaling, and modulate GABAergic receptor expression, and although the exact mechanisms remain unclear, neuromodulation is thought to be dependent on the type of eicosanoid prostaglandin PGE2 receptors (EPRs) stimulated (Ahmadi et al, 2002 ; Chen and Bazan, 2005 ; Laaris and Weinreich, 2007 ; Marty et al, 2008 ; Lin et al, 2014 ; Yang et al, 2015 ).…”
Section: Chorioamnionitismentioning
confidence: 99%
“…Similar to pro-inflammatory cytokines, PGE 2 can alter neuronal excitability and neurotransmission. PGE 2 has been shown to both enhance and inhibit glutaminergic transmission, depress glycingeric signaling, and modulate GABAergic receptor expression, and although the exact mechanisms remain unclear, neuromodulation is thought to be dependent on the type of eicosanoid prostaglandin PGE2 receptors (EPRs) stimulated (Ahmadi et al, 2002 ; Chen and Bazan, 2005 ; Laaris and Weinreich, 2007 ; Marty et al, 2008 ; Lin et al, 2014 ; Yang et al, 2015 ).…”
Section: Chorioamnionitismentioning
confidence: 99%
“…The supernatant was then resolved on 10% SDS-PAGE (Bio-Rad Laboratories, Inc., Hercules, CA, USA) and was subsequently immunoblotted with OATP1B3 (1:500 dilution) and Na-K-ATPase (1:8000 dilution; Abcam, Cambridge, MA, USA) antibodies. Na-K-ATPase was used as a loading control for surface protein levels of OATP1B3 [ 36 , 37 ]. The blots were also probed with a GAPDH antibody (1:1000 dilution, Santa Cruz, Dallas, TX, USA) to determine whether the surface fraction had intracellular protein contamination, similar to previously published.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that changes in both GABAAR function and expression are involved in hyperalgesia (Ran et al, 2014;Obradovic et al, 2015). Especially, pervious reports indicated that PGE 2 can modify the GABA-activated current (Yang et al, 2015). So, we first to test whether PGE 2 or Car/PGE 2 injection would change the function of GABAAR activation from analgesia to hyperalgesia.…”
Section: Function Of Gabaar In the L4-l6 Drgs Is Not Changed In Hyperalgesic Priming Modelmentioning
confidence: 96%